Appraisal of awareness on medical emergencies and its management among dentists in Bhubaneswar, India - Ramesh Nagarajappa; Ipsita Mahapatra; Dharmashree Satyarup; Sharmistha Mohanty (National Institute of Public Health - National Institute of Hygiene, 2021)
Background. Medical emergencies can be distressing for any dental professional, whether in a dental practice, hospital or other sites. Objectives. To assess the knowledge and awareness of dental practitioners towards medical emergencies and its management in Bhubaneswar. Material and Methods. In this cross-sectional investigation, a self-administered questionnaire which included demographic details and 19 questions regarding knowledge about medical emergencies, was disseminated to a random sample of 183 dentists working in their private dental clinic set up in Bhubaneswar. Chi-square test was used for statistical analysis. Results. Total sample size was 183, out of which 79 (43.17%) were males and 104 (56.83%) were females. The mean age was found out to be 30.7 ± 5.38 years. Practically 96% of the practitioners were not certain enough to deal with the emergency conditions at dental office. Around 67% had not attended any workshop on emergency training. It was amazing to observe that larger part (90%) of the experts didn't possess first aid kit at their dental office. In instances of handling emergency situation at the dental chair no statistical significance (p>0.05) with respect to age and gender was found. Conclusion. This investigation showed that hypothetically dental professionals had better knowledge on medical emergencies yet at the same time they were not equipped efficiently to manage the same at their workplace.